Les réformes contre le redoublement ou les limites des recherches non collaboratives - Sabine Kahn (Recherches en Éducation)
This paper studies how results obtained by research in education science are used by actors in the field of politics as well as in the domain of education. The case example studied here concerns research on pupils' repetition of a school year. A first observation shows that research on the question is abundant but has never given rise to collaborative forms of investigation. At the political level, research results are translated into instructions forwarded to teachers; these instructions take the shape of strategies to be implemented in their classes. Our inquiries reveal that despite a general attitude of "obedience" on the part of teachers, the orders are never carried out to the letter, but adapted to tie in with the demands of teaching practice. These adaptations, however, are not infrequently found to be counter-productive with regard to the aims originally pursued by the reforms.